St. Jude Medical Trifecta aortic valve: results from a prospective regional multicentre registry. Issue 1 (December 2015) - Mariscalco, Giovanni; Mariani, Silvia; Bichi, Samuele; Biondi, Andrea; Blasio, Andrea; Borsani, Paolo; Corti, Fabrizio; De Chiara, Benedetta; Gherli, Riccardo; Leva, Cristian; Russo, Claudio; Tasca, Giordano; et al.
Abstract Background The Trifecta aortic bioprosthesis (St. Jude Medical, Inc., St. Paul, MN, USA) is a stented pericardial heart valve with excellent preliminary results. Aim of the study was to evaluate its early clinical and hemodynamic performances in a multicenter regional registry. Methods Between January 2011 and June 2012, 178 consecutive patients undergoing aortic valve replacement with the Trifecta bioprosthesis were prospectively enrolled at 9 Italian centers. Clinical and echocardiographic data were collectedat discharge, 6-months and at 1-year postoperatively. Results The average age was 75.4 ± 7.7 years, and 95 (53 %) were men. Indication for valve replacement included stenosis in 123 patients (69 %), mixed lesions in 25 (14 %), and regurgitation in 30 (17 %). Ninety-three (52 %) patients were in NYHA functional class III/ IV. Hospital mortality accounted for 5 (2.8 %) patients. No valve-related perioperative complications were encountered. Median follow-up was 20.5 months (range: 1-34). Early (≤6 months) complications included one thromboembolic event, one major bleeding, and 3 endocarditis (2 explants). Two late (>6 months) thromboembolic events and two endocarditis (1 explant) were registered. No valve thrombosis or structural deterioration were observed after discharge. At 30-months, freedom from all-cause mortality was 87 %, freedom from valve-related mortality 99.4 %, freedom from endocarditis 97.5 %, and freedom from valve explants 98 %. At 1-year, mean gradients ranged from 8 to 16 mmHg, and effective orifice area indexes from 1.0 to 1.2 cm2 /m2 for valve sizes from 19 to27 mm, respectively. No patients had severe prosthesis-patient mismatch. Conclusions Trifecta bioprosthesis provided favourable clinical and hemodynamic results over time.